Agronomic characterization and responses to cofffeeleaf rust in coffee progenies resistant to the gall nematode Meloidogyne exigua - Rezende, Ramiro Machado; Carvalho, Gladyston Rodrigues; De Carvalho, Alex Mendonça [UNESP]; Mendes, Antônio Nazareno Guimarães; Salgado, Sônia Maria Lima; Botelho, Cesar Elias; Ferreira, Andre Dominghetti (Universidade Estadual de Londrina, 2017)
The aim of this study was to determine agronomic characteristics and responses to the cofffee leaf rust fungus (Hemileia vastatrix Berk. et Br.) in cofffee progenies resistant to the gall nematode Meloidogyne exigua. The experiment was conducted in December 2000 at Ouro Verde Farm (FazendaOuro Verde), located in the municipality of Campos Altos - Minas Gerais (MG). Ten F3:4 progenies were evaluated. They were derived from crosses between CIFC 2570 Timor Hybrid selections and Catuaí cultivars known to be resistant to M. exigua. The Catuaí Vermelho IAC 99 cultivar served as a control. A randomized block design with three replicates was used. In total, there were thirty-three plots consisting of eight plants each. The following characteristics were assessed between the harvests of 2011/2012 and 2014/2015: (a) yield expressed as processed cofffee bags ha-1; (b) rust incidence and severity; (c) vegetative vigor; (d) percentage of cofffee fruits at the cherry stage; (e) percentage of floaters; (f) crown diameter; (g) percentage of cofffee beans of size sieve 17 and higher; and (h) sensory analysis of the cofffee beverage. The results indicated the following: (a) the H514-7-14-2, H514-7-4-5, H493-1-2-2, H514-7-16-3, H514-7-8-11, H518-2-10-1, and H514-5-2-4 progenies were the most productive; (b) all progenies showed promising resistance to cofffee leaf rust; (c) all genotypes had the potential for specialty cofffee production; (d) the H493-1-2-2 progeny showed resistance both to rust and the nematode, and has good potential for specialty cofffee production; and (e) the yields of the H514-7-8-11, H518-2-10-1, H514-5-2-4, H514-7-16-3, H514-7-14-2, H514-7-4-5, and H493-1-2-2 progenies were significantly higher than that of the Catuaí IAC 99 control.
Keywords: Coffea arabica; Genetic breeding; Timor Hybrid; Yield